Two Novel Naphthalene Glucosides and an Anthraquinone Isolated from Rumex dentatus and Their Antiproliferation Activities in Four Cell Lines - Yanxia Han; Nan Li; Wenming Xu; Zengjun Guo; Ling Han; Nan Wu; Hui Zhang (Molecules, 2012)
An ethyl acetate extract of the roots of Rumex dentatus L. was investigated. Three compounds were identified by their spectroscopic data as chrysophanol (1), 6-methyl-7-acetyl-1, 8-dihydroxy-3-methoxy naphthalene-1-O-β-D(L)-glucoside (2) and 6-methyl-7-acetyl-1, 8-dihydroxy naphthalene-1-O-β-D(L)-glucoside (3) were found in the plant for the first time. Compounds 2 and 3 are novel compounds. Their antiproliferation activities were tested by the MTT assay in four cell lines (breast cancer MCF-7, gastric cancer 7901, melanoma A375 and oophoroma SKOV-3).